CLINICAL PHARMACOLOGICAL OPTIMIZATION IN CHRONIC HEART FAILURE: HEMODYNAMIC REMODELING AND NEUROHORMONAL MODULATION IN A REDUCED EJECTION FRACTION COHORT (World Bulletin of Public Health, 2026)
The pathophysiological progression of chronic heart failure with reduced ejection fraction dictates a mandatory, aggressive pharmacological blockade of maladaptive neurohormonal pathways. This study evaluates the precise clinical and hemodynamic outcomes of deploying a rapid, simultaneous initiation strategy of foundational disease-modifying therapies compared to traditional, sequential up-titration. A prospective clinical analysis was conducted involving 138 adult patients diagnosed with symptomatic heart failure (baseline left ventricular ejection fraction < 40%). Subjects were stratified into two clinical pathways: a conventional sequential titration cohort (n=66) and a rapid simultaneous initiation cohort (n=72) utilizing a quadruple therapy protocol (Angiotensin Receptor-Neprilysin Inhibitors, beta-blockers, mineralocorticoid receptor antagonists, and SGLT2 inhibitors) guided by strict pharmacokinetic and hemodynamic monitoring. Clinical data indicate that aggressive, early neurohormonal modulation significantly accelerates reverse myocardial remodeling without exacerbating renal or hypotensive adverse events. The rapid initiation cohort demonstrated a profound 48.6% reduction in circulating N-terminal pro-b-type natriuretic peptide levels within the first 90 days, directly correlating with an absolute left ventricular ejection fraction improvement of 8.4 ± 1.2% (p = 0.011). Conversely, the standard sequential group exhibited delayed symptomatic relief and higher rates of early hospital readmission. The dynamics of the observed results suggest that the historical paradigm of cautious, step-bystep pharmacological titration deprives patients of early synergistic physiological benefits. Comprehensive pharmacotherapy must prioritize the rapid, parallel integration of all foundational drug classes, individually calibrated against baseline blood pressure and renal clearance, to halt myocardial degradation and optimize long-term survivability.